Development of Model Blended Learning in Cooperative Learning for Technology and Engineering Skills in Vocational Education - Suartini, Tuti; Evlyanti, Sisca; Ahmad Juanda, Enjang; Sukandar, Aan; Pramanik, Tari (International Journal of Psychosocial Rehabilitation, 2020)
Increasing the interest and willingness of students to learn material was determined from the behavior of students in using information communication technology. The learning model developed was a cooperative learning model based on blended learning. Utilization of information technology, by not leaving the pattern of direct guidance from instructors and the use of learning resources to improve literacy mastery of abilities in technology and engineering, became important. The Research and Development (R&D) procedure used a blended learning cooperative learning model design in the form of online and face-to-face learning for ICT literacy subjects and learning media in the experimental and control classes. Blended learning-based cooperative learning models were carried out with scenarios, namely offering participation in the experimental class, forming learning groups, and learning activities (lecturers, group tutor teams, students, evaluations). The purpose of this research is to get the quality of learning activities. In stage I, students were offered to take the experimental class and the Control class. The study was conducted with 16 students taking experimental classes and 21 taking control classes. Based on the results of the study, the level of mastery of literacy of ICT and media (n-gain) learning in the experimental class was higher than in the control class.